Novel use of Quillaja saponaria extracts to prevent viral infections in Atlantic salmon: in vitro ISAv and IPNv inhibition and in vivo protection against IPNv - Schlotterbeck, Trinidad; Cortés, Hernán; Cañon-Jones, Hernan; San Martín, Ricardo; Padilla, Leandro; Castillo-Ruiz, Mario (Frontiers in Veterinary Science, 2026)
IntroductionThe global expansion of salmon farming has increased the prevalence of viral diseases, especially Infectious Pancreatic Necrosis (IPN) and Infectious Salmon Anemia (ISA), posing significant threats to the sustainability and productivity of the industry. Extracts from the Chilean tree Quillaja saponaria Molina are a rich source of triterpenic saponins, glycosides with antimicrobial and immunomodulatory properties. This study assessed the antiviral efficacy of a non-purified (NPQ), a partially purified (PPQ, the active ingredient of PAQ-Xtract®), and a purified (VaxSap®) commercial Quillaja saponaria extracts, as dietary additives to prevent and control viral infections in Atlantic salmon (Salmo salar).MethodsThe In vitro antiviral activity of the extracts was measured through infection assay in ASK and CHSE-214 cell lines. Results were expressed as the percentage of inhibition, comparing the number of viral copies or the number of PFU produced in untreated conditions to those in Quillaja saponaria extracts treated conditions. In vivo trial were conducted on Atlantic salmon fry. During the trial, fish were fed with a standard diet and supplemented with NPQ or PPQ. Fishes were intraperitoneal challenged with IPNv and mortalitiy registered.ResultsIn vitro assays demonstrated that Quillaja extracts generated over 90 and 60% inhibition of replication of ISAv and IPNv, respectively. In vivo challenge experiments further showed that dietary supplementation with NPQ or PPQ significantly reduced cumulative mortality following IPNv infection compared with untreated controls.DiscussionThese findings indicate that Quillaja saponaria extracts may be used as effective, natural, non-pharmacological additives to prevent diseases caused by these viruses. Their use supports the development of sustainable and environmentally responsible disease-management strategies in modern aquaculture.